Pendidikan Emansipatoris Bagi Anak Rentan Bekerja: Telaah Kritis dalam Perspektif Paulo Freire - Nursaptini Nursaptini; Rukiyati Rukiyati (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
Children vulnerable to work face multiple barriers to meaningful education due to poverty, marginalization, limited access to schooling, and other forms of social vulnerability. Although previous studies have emphasized the importance of education as a strategy for child protection, most have primarily focused on expanding educational access and school participation, while limited attention has been given to learning processes that empower students. This study aims to synthesize the literature on education for children vulnerable to work and Paulo Freire’s critical pedagogy to develop a conceptual framework of emancipatory education relevant to this population. A narrative review approach was employed by analyzing scholarly publications retrieved from Scopus, Web of Science, ERIC, and Google Scholar. The selected literature was screened based on its relevance to children vulnerable to work, Freirean pedagogy, and emancipatory education, and subsequently analyzed through thematic categorization, conceptual synthesis, and critical interpretation. The findings indicate that research on children vulnerable to work has predominantly adopted child protection and educational access perspectives, whereas studies on Freire’s pedagogy emphasize dialogical education, problem-posing education, critical consciousness, praxis, and humanization as the foundations of emancipatory learning. Integrating these two bodies of literature resulted in the Conceptual Model of Emancipatory Education for Children Vulnerable to Work, which positions students’ lived experiences as the starting point of learning, followed by dialogue, the development of critical consciousness, praxis, and humanization to foster student empowerment and social transformation. This model extends the existing literature by integrating the issues of children vulnerable to work and Freirean critical pedagogy into a coherent conceptual framework. The findings provide theoretical, pedagogical, and policy implications for developing more contextual, inclusive, and empowering educational practices for children vulnerable to work.